Implementasi Rekam Medis Elektronik Di Puskesmas SP Kota SMD - Noufhal, Noufhal; Husin, Husin (Politeknik Unggulan Kalimantan, 2025)
The implementation of electronic medical records (EMR) aims to accelerate services and improve the quality of services at the Health Center. Conceptually, EMR makes it easier for officers to work, shortens data distribution time and minimizes file storage space. This study aims to evaluate the implementation and storage of EMR at the SP Health Center in SMD City. The study used a qualitative approach with a phenomenological design, data collection techniques with observation and interviews with 4 informants selected purposively. The main research instrument was the researcher himself supported by interview and observation guidelines. The data analysis used the Miles and Hubberman approach. The results of the study revealed that there were still incomplete clinical information filling and electronic medical records did not support electronic signatures and the security of medical records was not guaranteed so that the implementation of filling in clinical information and storing electronic medical records had not gone well. Examining this matter requires emphasis and monitoring of health workers who fill in and store them.